2013
DOI: 10.4314/wsa.v39i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Growth, phenological and yield responses of a bambara groundnut (<i>Vigna subterranea</i> L. Verdc) landrace to imposed water stress: II. Rain shelter conditions

Abstract: Bambara groundnut is a protein-rich legume, with food-security potential. Effects of irrigation levels and seed coat colour on growth, development, yield and water-use efficiency of local bambara groundnut landrace selections were evaluated under a rain shelter. Emergence was slow, although variation was indicated between landraces. Limited water availability was shown to lower stomatal conductance, although chlorophyll content index was shown to be unaffected. Additionally, growth indices of plant height, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 31 publications
1
39
1
3
Order By: Relevance
“…Reported drought responses displayed in bambara groundnut include; reduced vegetative period, early flowering, reduced reproductive stage and also an earlier final maturity date in response to water stress (Mabhaudhi et al 2013). Landraces from Jozini, South Africa, such as 'Red' and 'Brown' landraces had an earlier maturity date (p \ 0.01) when the plants were stressed at 30 % of the crop water requirement (ETa; mean: 122.75 DAP) as compared to 100 % ETa (mean: 128 DAP) (Mabhaudhi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported drought responses displayed in bambara groundnut include; reduced vegetative period, early flowering, reduced reproductive stage and also an earlier final maturity date in response to water stress (Mabhaudhi et al 2013). Landraces from Jozini, South Africa, such as 'Red' and 'Brown' landraces had an earlier maturity date (p \ 0.01) when the plants were stressed at 30 % of the crop water requirement (ETa; mean: 122.75 DAP) as compared to 100 % ETa (mean: 128 DAP) (Mabhaudhi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Landraces from Jozini, South Africa, such as 'Red' and 'Brown' landraces had an earlier maturity date (p \ 0.01) when the plants were stressed at 30 % of the crop water requirement (ETa; mean: 122.75 DAP) as compared to 100 % ETa (mean: 128 DAP) (Mabhaudhi et al 2013). Paraheliotropic movement has been observed in some drought-stressed bambara groundnut landraces, such as AS-17 (Stadler 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soils at Ukulinga were described as shallow clayey to clayey loam with medium fertility (Mabhaudhi et al, 2013), which was matched with Clay_Shallow_MF_101mm (Table 2) in the APSIM soil file. Soils from Richards Bay were described as relatively deep and sandy with low fertility (Motsa et al, 2015), and were matched to Sandy_Medium_LF_111 mm (Table 3) in the APSIM soil file.…”
Section: Soilmentioning
confidence: 99%
“…Seeds of a locally grown bambara groundnut landrace were collected from subsistence farmers in Jozini (27°26′ S, 32°4′ E), KwaZulu–Natal, and sorted into three distinct colors: Red, Light brown and Brown. The three seed colors were used in pot (Mabhaudhi et al, 2011), field (Mabhaudhi and Modi, 2013), and rain shelter studies (Mabhaudhi et al, 2013) to develop model inputs. The results from these experiments showed that the Red landrace selection was adapted to water‐limited conditions and was possibly drought tolerant.…”
Section: Methodsmentioning
confidence: 99%